Public Perceptions of Legal Aspects of Price Tagging of Balinese Betutu Chicken - Simon Nahak; Agus Darma Yoga; Mirsa Umiyati (Jurnal Hukum Prasada, 2021)
This study aims to determine community perceptions about the legal aspects of price tagging in Balinese chicken Betutu sales. The population of this study was housewives in Banjar Anyar, Sumertha Kelod Village, East Denpasar District, Denpasar, Bali. This study used a survey sample (cross sectional study). The variables of this study are: (1) The importance of giving price tags; (2) Without the label violating the law; (3) The constitution on the sale of goods. Based on the analysis, the results of this study indicate that as much as 65% of respondents consider the price tagging important in sales and 3.9% of the 103 respondents consider that the price tagging in selling Balinese chicken Betutu is less important. Meanwhile, at the level of understanding without labels violating the law, 55.3% of respondents did not know that without a label in selling Balinese chicken betutu was against the law and only 14.6% of respondents knew that without a label in selling Balinese chicken Betutu was against the law. At the level of understanding of the laws on the sale of goods, 77.7% of respondents did not know about the laws on selling goods and only 4.9% of respondents knew about the laws on selling goods. Based on these results it can be concluded that there are still many people who do not know the importance of labeling a business product and the legal aspects of labeling a business product.